Перевод новеллы Томаса Манна «Смерть в Венеции» на языки других искусств - Баринова, Е. (Літературознавчі обрії. Праці молодих учених, 2010)
Thomas Mann’s works remain extremely popular nowadays, which can be proved by the fact that representatives of different arts, such as artists, film directors, composers etc. continue using and interpreting his motives and ideas. The analysis of «translations» of Thomas Mann’s works into languages of other arts reveals new depths in his works as well as the peculiarities of the cultural background and views of the recipient. All the writings analyzed in the article represent wonderful examples of intercultural and cross-art communication.